EndoLive UK 2015: introducing the best of UK endoscopy to the world. Issue 2 (18th May 2015) - Smith, Philip J
Abstract : The inaugural EndoLive UK held in the International Convention Centre (ICC) Birmingham on the 12–13 March 2015 was a watershed moment for UK endoscopy and for the British Society of Gastroenterology (BSG). The event provided the perfect platform to demonstrate how the UK is delivering some of the highest quality endoscopic practice, training and research in the world. Organised by UK endoscopy experts and supported by internationally renowned endoscopists such as Professors Paul Fockens, Douglas Rex and Peter Siersema, EndoLive UK pushed back the boundaries of innovation and interaction during a 'Live Endoscopy' event. Frontline Gastroenterology supported the event with a special edition of this journal dedicated to Endoscopic Practice in April 2015. With over 500 people from around the globe attending this first event, the aim of highlighting the very best of UK endoscopy on a national and international stage was achieved. Furthermore, the educational content of the course was developed to be accessible and appropriate to a variety of clinicians with different levels of experience—endoscopy trainees, nurses, General practitioner (GP) endoscopists, gastroenterologists and surgeons. This article reviews this event and its many highlights and successes.